"HINGE HOUSE": Space embracing plural people, activities, and objects by devising a timber frame joint. Issue 1 (9th December 2020) - Tachibana, Mio; Tsuboi, Hirotsugu
Abstract: We designed a house that embraces plural people, activities, and objects and where people act autonomously in a suburb of Tokyo. A new hinge joint and innovative timber framework were devised to implement the liberated ample space, and environmental strategies were adopted. Abstract : By devising new hinge joints and innovative timber framework, we designed a house that embraces plural people, activities, and objects and where people act autonomously in a suburb of Tokyo.